SOCIO-PHILOSOPHICAL ANALYSIS OF RELATIONSHIPS RELATED TO WIVES AND GIRLS IN MODERN UZBEKISTAN - Jumaniyazova Mokhira (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
Today’s modern society observes we are First of all , this is us society organize doer persons and their mutually relationships our learning great important _ Because of the society decision to find and development him organize doer of individuals to the activity organic depends . In this place Modern in Uzbekistan decision found society itself _ activity mechanism there is of society activity mechanism we mean it there is social relationships and interpersonal of relationships structure in society generally accepted done democratic views mean we hold.